Literature Review on Deep Learning in Madrasah Ibtidaiyah: Meaningful, Mindful, and Joyful Learning Perspectives - Nopiyanti; Evi Maulidah (Amorti: Jurnal Studi Islam Interdisipliner, 2026)
he lack of active participation and meaningful engagement in the learning process of Madrasah Ibtidaiyah students highlights the need for a transformation toward a deeper, more contextual, and student-centered learning approach. This study aims to examine the implementation of deep learning in the context of Madrasah Ibtidaiyah education through the integration of three core approaches: meaningful learning, mindful learning, and joyful learning. This research employs a literature review method, analyzing 20 relevant national and international scholarly articles. Data were collected from digital databases such as Google Scholar, ResearchGate, and Sinta, with publications ranging from 2020 to 2025. The selected literature includes national and international journals. Thematic content analysis was used to identify conceptual patterns related to deep learning. The findings reveal that the synergy of the three approaches significantly enhances student participation, deepens conceptual understanding through real-life relevance, and fosters reflective learning awareness in a joyful atmosphere. Therefore, deep learning is considered effective in strengthening active, authentic, and meaningful learning practices at the Madrasah Ibtidaiyah level. As a recommendation, future research should test the effectiveness of the deep learning approach in classroom settings through quantitative methods or classroom action research, as well as develop appropriate evaluation instruments to support its sustainable implementation in Madrasah Ibtidaiyah.